2014
DOI: 10.1002/ajh.23651
|View full text |Cite
|
Sign up to set email alerts
|

Azurophilic granules in myeloma cells

Abstract: The neoplastic cells of multiple myeloma (plasma cell myeloma) show a wide range of cytological abnormalities. These include cytoplasmic inclusions composed of immunoglobulin, which may be either crystalline or globular, the latter either clearly in the cytoplasm (Russell bodies) or invaginated into the nucleus (Dutcher bodies). A distinctive type of rod-shaped azurophilic inclusion does not represent immunoglobulin but rather is lysosomal in origin [1].In this patient with immunoglobulin G kappa myeloma a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The significance of the presence of cytoplasmic granules in myeloma cells is poorly understood. The GM cells are considered to be detectable infrequently because the study about large number of cases with the GM cells has not been demonstrated, and only several cases with cytoplasmic granules in myeloma cells were reported . In our study, 20.5% of MM patients displayed cytoplasmic granules, and hence we speculated that GM cells could be detected occasionally.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The significance of the presence of cytoplasmic granules in myeloma cells is poorly understood. The GM cells are considered to be detectable infrequently because the study about large number of cases with the GM cells has not been demonstrated, and only several cases with cytoplasmic granules in myeloma cells were reported . In our study, 20.5% of MM patients displayed cytoplasmic granules, and hence we speculated that GM cells could be detected occasionally.…”
Section: Discussionmentioning
confidence: 58%
“…Granules are detected in the cytoplasm of myeloma cells by May‐Giemsa staining in some cases. Since the first identification of granule‐containing myeloma cells by Steinmann, several case reports about granule‐containing myeloma have been published . However, the clinical features of granule‐containing myeloma cells have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Cytoplasmic crystalline inclusion bodies in neoplastic plasma cells are not a rare event. activity, also demonstrated in our case [1][2][3]. Its prognostic values has not been investigated because of its rarity.…”
mentioning
confidence: 65%